TO THE METHODOLOGY FOR SEPARATION OF MIGRATING POPULATION COMPLEXES OF THE OKHOTSK SEA PINK SALMON IN THE PACIFIC WATERS AT KURIL ISLANDS USING THE GONAD-SOMATIC INDEX - E. A. Shevlyakov; M. G. Feldman; V. A. Shevlyakov; A. N. Kanzeparova (Известия ТИНРО, 2020)
New method is proposed for operational differentiation of pink salmon runs with different time of spawning and different state of gonads measured quantitatively with a gonad-somatic index. Results of this new method and traditional methods of differentiating are compared. The conception of spatial niches in the Pacific waters adjacent to Kuril Islands for certain temporal groupings of the Okhotsk Sea pink salmon is critically revised on the base of these new results. The runs cannot be separated using any fixed value of the gonad-somatic index. The zones of different groupings could be spatially overlapped. The method is tested on the data of trawl survey conducted aboard RV Professor Kaganovsky in May-July 2018, during anadromous migration of pink salmon, and shows a high compliance with the regional groupings ratio determined on the data of pink salmon catch in the Okhotsk Sea and their escapement to rivers. Tendency of the late-maturing forms of pink salmon to migrate through the southern Kuril waters is confirmed, whereas the portion of early-maturing pink has increased toward the Ocean.